Assessment of vehicle emission programs in China during 1998–2013: Achievement, challenges and implications. (July 2016) - Wu, Xiaomeng; Wu, Ye; Zhang, Shaojun; Liu, Huan; Fu, Lixin; Hao, Jiming
Abstract: China has been embracing rapid motorization since the 1990s, and vehicles have become one of the major sources of air pollution problems. Since the late 1990s, thanks to the international experience, China has adopted comprehensive control measures to mitigate vehicle emissions. This study employs a local emission model (EMBEV) to assess China's first fifteen-year (1998–2013) efforts in controlling vehicles emissions. Our results show that China's total annual vehicle emissions in 2013 were 4.16 million tons (Mt) of HC, 27.4 Mt of CO, 7.72 Mt of NOX, and 0.37 Mt of PM2.5, respectively. Although vehicle emissions are substantially reduced relative to the without control scenarios, we still observe significantly higher emission density in East China than in developed countries with longer histories of vehicle emission control. This study further informs China's policy-makers of the prominent challenges to control vehicle emissions in the future. First, unlike other major air pollutants, total NOX emissions have rapidly increased due to a surge of diesel trucks and the postponed China IV standard nationwide. Simultaneous implementation of fuel quality improvements and vehicle-engine emission standards will be of great importance to alleviate NOX emissions for diesel fleets. Second, the enforcement of increasingly stringent standards should include strict oversight of type-approval conformity, in-use complacence and durability, which would help reduce gross emitters of PM2.5 that are considerable among in-use diesel fleets at the present. Third, this study reveals higher HC emissions than previous results and indicates evaporative emissions may have been underestimated. Considering that China's overall vehicle ownership is far from saturation, persistent efforts are required through economic tools, traffic management and emissions regulations to lower vehicle-use intensity and limit both exhaust and evaporative emissions. Furthermore, in light of the complex technology for emerging new energy vehicles, their real-world emissions need to be adequately evaluated before massive promotion. Highlights: NOX emissions have rapidly increased for lacking adequate controls for HDDVs. HC emissions are higher than previous estimates using updated evaporative emission data. Emission density in the East China is significantly higher than developed countries. Vehicle emissions are greatly reduced compared to non-control scenarios. Abstract : Our multiple-year emission inventory indicates a rapid increase in NOx emissions from total vehicles in China and underestimated HC emissions by previous estimates over the past decade.